Pedagogía clínica – hospitalaria. Atención al alumno – paciente con N. E. E. transitorias - Mendoza Carrasco, Mariella Victoria (2014)
Nowadays, health related with educationis an important subject, the distinguishingarea of pedagogy that is in charge of sickor hospitalize child education, take carethe patient child so that hi/her holds upneither his/her personal development norhis/her learning, at the same time it traysto taking care to psychological and socialneeds generated by the hospitalizationand whit the specific sickness hi/hersuffers.